Occurrence of male-specific and somatic coliphages and relationship with rainfall in privately-owned wells from peri‑urban and rural households. (1st August 2021) - Stallard, Megan A.; Mulhern, Riley; Greenwood, Emily; Franklin, Taylor; Engel, Lawrence S.; Fisher, Michael B.; Sobsey, Mark D.; Zanib, Hania; Noble, Rachel T.; Stewart, Jill R.; Sozzi, Emanuele
Highlights: E. coli in private drinking water wells is rare, but total coliforms are present. Viruses that infect coliform bacteria ( E. coli ) were detected in over half of samples. Both elevated monthly rainfall levels and coliphage concentrations are associated. Coliphages should be included in a monitoring program to protect well water users. Abstract: Privately-owned drinking water wells serving fewer than 25 people (private wells) are prevalent and understudied across most of the US. Private wells primarily serve rural households located outside of municipal drinking water and sewerage service coverage areas. These wells are not regulated by United States Environmental Protection Agency (EPA) under the Safe Drinking Water Act, are not regularly monitored by any public agency or utility, and generally do not undergo disinfection treatment. Coliphages are a group of viruses that infect coliform bacteria and are useful viral surrogates for fecal contamination in water systems in much the same way that fecal indicator bacteria (FIB), such as E. coli and to a lesser extent total coliforms, are used to quantify fecal contamination. Coliphages are approved by the EPA for regulatory monitoring in groundwater wells in the USA, but are not routinely used for this purpose. The present study characterizes the occurrence of male-specific and somatic coliphages, along with FIB, in private wells ( n = 122) across two different counties in North Carolina. While occurrences of E. coli were rare and frequency of total coliform was generally low ( 20%), male-specific and somatic coliphages were detectable in 66% and 54% of samples, respectively. Concentrations of male-specific coliphages were higher than somatics at each county and on a monthly basis. Rainfall appears to be partly influencing higher coliphage concentrations in December, January and February. This research underscores the need for increased surveillance in private wells and consideration of using coliphages in order to better characterize occurrence of fecal contamination at the time of sampling, especially during rainier months. Graphical abstract: Image, graphical abstract